Pengaruh Perputaran Kas, Perputaran Piutang, dan Perputaran Persediaan Terhadap Profitabilitas pada PT. Mayora Indah Tbk - Wahyul, Adella; Wahab, Wahyul (CIVITAS: Jurnal Studi Manajemen, 2021)
The purpose of this research is to know how the effect of cash turnover, receivable turnover, and inventory turnover to profitability on PT Mayora Indah Tbk simultaneously and partially. Data analysis used multiple linear regression test, data processing using SPSS Statistics. The result showed that partial cash turnover and receivable turnover have no effect and were not significant to profitability, while inventory turnover has a positive and significant effect to profitability. Meanwhile, simultaneously cash turnover, receivable turnover, and inventory turnover has a positive and significant effect to profitability.